OPINIONS AND IMPRESSIONS OF PARENTS ON THE REALIZED SCIENTIFIC ACTIVITIES - COOPERATION OF PARENTS, CHILDREN AND FUTURE EDUCATORS AND TEACHERS - Miletić, Andrijana; Milanović, Nedeljko (Metodička teorija i praksa, 2024)
Abstract: The focus of this paper is directed towards the opinions and impressions of parents about participation in scientific activities through the cooperation of parents, children and future educators and teachers. Students of the Faculty of Education in Jagodina, future educators and teachers organized and realized a scientific workshop that enabled children to learn and explore about different properties of materials and movement, as well as the active participation of parents in the same. A total of 18 parents participated in the research. The results show the positive impressions of the parents about their participation and the enthusiasm of the children who enjoyed the various activities. The conducted scientific activities are one of the examples of good practice through the cooperation of parents, children and future educators and teachers, whose example could be followed by other practitioners promoting the productive use of leisure time.
Keywords: parents; children; students; leisure time; scientific activities